Design and Development of a Web-Based Community Complaint Information System (SIPMAS) - Rivandi Ilham; Enrico Abdillah N. P; Muhammad Rama Prasetyo; Bagus Tri Mahardika; Yan Sofyan Andhana Saputra (JEPTIRA, 2026)
This study aims to design and develop a web-based public complaint information system named SIPMAS (Sistem Informasi Pengaduan Masyarakat). Previously, municipal and infrastructural grievances in target community sectors were communicated through physical paperwork or unstructured short messaging services, causing immense delays, loss of data tracking, and a lack of transparency. The system was engineered using the Laravel framework, PHP, and a MySQL relational database following the Model-View-Controller (MVC) software design pattern. System evaluation was conducted using functional Black Box testing and deployment response tracking metrics. The results indicate that the SIPMAS portal successfully provides a centralized community environment featuring structured grievance logging, automated urgency sorting, and status validation tracking logs, while offering an administrative control dashboard for comprehensive mitigation management. This digital architecture assists regional administrators in processing neighborhood infrastructure issues more transparently and efficiently, thereby enhancing community administrative accountability.